Veterinary Medicine and Pharmaceuticals (IntechOpen, 2021)
Veterinary pharmaceuticals provide animals with the requisite, complete animal health care. The availability of safe and good quality medicines in the right amounts is needed in achieving optimum animal health care. The economic benefits of animal food products cannot be under-estimated. Veterinary pharmaceuticals are needed to meet the ever-growing demand of animal protein for the human population. However, their routine and unguarded use play significant roles in many public health issues, such as antimicrobial resistance. The practices, knowledge, and awareness needed on the use and application of veterinary pharmaceuticals amongst farmers, animal health professionals, microbiologists, and policy makers remain key in ensuring a safe and healthy food chain for all. In the field of veterinary medicine, canine practice is a challenge to veterinarians. In recent years, newer diagnostic methods and therapeutic protocols have been published on a regular basis. Along with the existing knowledge of important canine diseases like ascites, duodenal disorders, pericardial effusions, and canine mastitis, this book is supplemented with all the latest information. Discussion of duodenal disorders in dogs, including IBD and SIBO, is an important topic in day-to-day practice. Ascites and mastitis in dogs are also important topics and are discussed in this book. Each topic carries practical points for the diagnosis and management of important diseases of dogs. Hence, this book will be very useful for canine practitioners.